Feelings undergone by the father at the birth of his child - Jovanka Bittencourt Leite de Carvalho; Rosineide Santana de Brito; Ana Cristina Pinheiro Fernandes Araújo; Nilba Lima de Souza (Rev Rene)
The aim of this study was to analyze fathers feelings at the birth of their children. It is a qualitative study conducted at two public institutions in Natal, RN. Ten fathers who were present during the birth of their children took part in the study. The data were collected in November and December 2004 using a semi-structured interview. The discourses were treated by content analysis using symbolic interactionism approach. The discourses revealed that the fathers who are present at their children’s birth, experience emotions of happiness and anxiety, along with fear, nervousness and concern. From the perspective of symbolic interactionism, the subjects interacted in the context of parturition according to their interpretation of the delivery as a happy and changing factor. Therefore, for the couple, the arrival of a child amidst the family, represents a life transforming stage intermingled with feelings directed towards the mother and child.